PENENTUAN NILAI HARGA WAJAR SAHAM DALAM RANGKA PENGAMBILALIHAN PADA TRIMEGAH SEKURITAS - Suryanto Gunawan; Renti Maharaini Kerti (Reformasi Hukum Trisakti, 2025)
In the acquisition of PT Trimegah Sekuritas Tbk, the tender price offered by the new controlling shareholder was set at Rp 218 per share. The issues raised include whether the determination of a fair share price in PT Trimegah Sekuritas Tbk's mandatory tender offer aligns with Article 17 letter a of POJK No. 09/POJK.04/2018 on the Acquisition of Public Companies, and whether the acquisition price of PT Trimegah Sekuritas Tbk’s shares must be disclosed in the Acquisition Plan Report under the transparency principle. The research adopts a descriptive normative method, using primary and secondary data analyzed through qualitative methods, with conclusions drawn deductively. The findings show that according to Article 7 paragraph (1) a jo. Article 17 a point 1 a of POJK No. 09/POJK.04/2018, the price used should be the highest among three options: the highest average daily trading price over the 90 days prior to the acquisition announcement, the highest average before the negotiation announcement, or the acquisition price already set. Disclosure of the share price during the negotiation stage is not required under the prevailing regulations, although many companies include it in the Acquisition Plan Disclosure to maintain transparency and investor confidence.